PASTORAL KONSELING KEPADA REMAJA (ANAK PENDETA) YANG MENGALAMI KRISIS IDENTITAS - Martiny Tumurang; Wolter Weol; Luma, Subaedah (PT. Giat Konseling Nusantara, 2024)
A Pastor's child is the child of a public figure where the pastor figure is respected and seen by many people, including the congregation. This depiction shows that a pastor is highly respected and held in high esteem by his congregation, as is the case with a pastor's child. The Pastor's son must maintain the good name of his family, which in fact is the Pastor. This makes him inevitably have to follow the same good qualities as his parents. A Pastor's child is a child born to a respected figure among the congregation. This kind of view actually shows that the Pastor's child is known to the congregation and also to the Pastors who are colleagues in ministry. So it is certain that a good attitude not to embarrass parents is important for a pastor's child. There are teenagers who are children of Pastors who say that their parents do not force them to behave like their parents, but the pressure of social and cultural views regarding Pastors is very strongly embedded in the life of society (congregation). Based on the public's view which states that the Pastor is an authoritative and well-known figure among the congregation and ultimately this view is given to teenagers who are the Pastor's children. Sometimes the congregation demands a lot so that the teenager will do what the congregation wants. Like it or not, they have to follow the existing rules in congregational life so that teenagers feel they are not free to express themselves.